SCIENTIFIC RATIONALE FOR TARGETED VITAMIN A SUPPLEMENTATION TO CHILDREN IN INDIA - Kapil, Umesh; Tyagi, Mamta (Indian Journal of Community Health, 2011)
In India, presently Vitamin A deficiency (VAD) is common amongst young children belonging to the underprivileged populations. The risk of deficiency is greatest in children under three years because their requirements are relatively higher and dietary intake is low. Also, these have higher risk of illnesses such as diarrhea, acute respiratory tract infection and measles, which deplete vitamin A reserves. In India, Severe deficiency of VA with corneal involvement was an important cause of nutritional blindness in sixties and early seventies children amongst children belonging to poor communities however presently, this is an extremely rare disease.